2021
DOI: 10.1111/1755-0998.13430
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking bioinformatic tools for fast and accurate eDNA metabarcoding species identification

Abstract: Environmental DNA (eDNA) metabarcoding is a promising approach to identify species within communities and can be used to evaluate biodiversity through a variety of estimators (Boulanger et al., 2021;Deiner et al., 2020;Pawlowski et al., 2018). The approach is based on the collection of environmental samples (e.g., soil, air or water) that contain the target organisms' DNA. After DNA extraction, DNA amplification with primers designed for a specific taxonomic group is performed and submitted to high-throughput … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 93 publications
2
50
2
Order By: Relevance
“…Dully et al (2021a; showed that MLbased pipelines are sufficiently robust even for rarefied samples. Other authors reached similar conclusions (Cordier et al, 2019a;Apothéloz-Perret-Gentil et al, 2021;Frühe et al, 2021;He et al, 2021) and Mathon et al (2021) reviewed literature on "eDNA and Machine Learning." In ML analysis, data is first pre-processed with common bioinformatic pipelines as for general metabarcoding analysis (Mathon et al, 2021) and subsequently processed through an automated DNA-Barcode Classifier (taxonomy assignment).…”
Section: Artificial Intelligence For Environmental Dna Analyses and Integration With Imaging Datasupporting
confidence: 60%
“…Dully et al (2021a; showed that MLbased pipelines are sufficiently robust even for rarefied samples. Other authors reached similar conclusions (Cordier et al, 2019a;Apothéloz-Perret-Gentil et al, 2021;Frühe et al, 2021;He et al, 2021) and Mathon et al (2021) reviewed literature on "eDNA and Machine Learning." In ML analysis, data is first pre-processed with common bioinformatic pipelines as for general metabarcoding analysis (Mathon et al, 2021) and subsequently processed through an automated DNA-Barcode Classifier (taxonomy assignment).…”
Section: Artificial Intelligence For Environmental Dna Analyses and Integration With Imaging Datasupporting
confidence: 60%
“…Raw forward and reverse reads were trimmed, merged, and classified using the Barque v1.7.0, an eDNA metabarcoding pipeline (Mathon et al, 2021;www.github.com/enorm andea u/barque).…”
Section: Bioinformatics Analyses and Data Cleaningmentioning
confidence: 99%
“…The trimmed paired‐end reads were then merged using flash v. 1.2.11 (options: − t = 1, − z , − m = 30, − M = 280). The merged reads were kept if they possessed both forward and reverse amplicon primer sequences using the 03_split_amplicons.sh script from Barque 1.5.2 (https://github.com/enormandeau/barque), an eDNA analysis pipeline that has been shown to be more accurate and efficient alternative to some highly used pipelines for analysing fish eDNA metabarcoding data (Mathon et al, 2021). Chimeras were removed with vsearch v. 2.5.1 (options: ‐‐uchime_denovo and ‐‐nonchimeras).…”
Section: Methodsmentioning
confidence: 99%